Respuesta :

Answer:

[tex]2x\³ + 3x\² = x(x\²) + (x- 2)\²[/tex] is not quadratic

Explanation:

Given

[tex]2x\³ + 3x\² = x(x\²) + (x- 2)\²[/tex]

Required

Determine if it is quadratic

We have:

[tex]2x\³ + 3x\² = x(x\²) + (x- 2)\²[/tex]

Open brackets

[tex]2x\³ + 3x\² = x^3 + x^2 - 4x + 4[/tex]

Collect like terms

[tex]2x\³ - x^3 + 3x\² -x^2 + 4x - 4=0[/tex]

[tex]x^3 + 2x\²+ 4x - 4=0[/tex]

A quadratic equation is represented as:

[tex]ax^2 +bx + c =0[/tex]

Hence:

[tex]x^3 + 2x\²+ 4x - 4=0[/tex] is not quadratic

ACCESS MORE